COMPARATIVE ANALYSIS OF CASH-DRIVEN RESILIENCE DURING THE COVID-19 PANDEMIC - Troi, Tania Liliani; Imelda, Elsa (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to examine the comparison and differences in levels of cash-driven resilience during the normal period, the period before the COVID-19 pandemic, and the period during the COVID-19 pandemic; profitability (return on assets, profit margin, and productivity of assets) and financial constraints (liquidity and leverage) on cash-driven resilience. This research method uses the purposive sampling technique. The number of samples used in this study was 86 manufacturing companies listed on the Indonesia Stock Exchange consecutively from 2018 to 2020. The analysis used in this study was descriptive statistics, Kruskal-Wallis test, and post hoc test which was processed with the help of IBM SPSS Statistics 26 software. This study found that overall, there are significant differences in cash-driven resilience during the normal period, the period before the COVID-19 pandemic, and the period during the COVID-19 pandemic; return on assets, profit margin, liquidity, and leverage on cash-driven resilience. While, productivity of assets does not have a significant difference on cashdriven resilience.